lncRNA-associated ceRNA network revealing the potential regulatory roles of ferroptosis and immune infiltration in Alzheimer’s disease - Tan, Yejun; Tang, Wang; Xiao, Wenbiao; Huang, Roujie; Li, Xin; Peng, Weijun; Yan, Kuipo; Cao, Yuan; Zeng, Yi; Kang, Jin (Frontiers in Aging Neuroscience, 2023)
Background Alzheimer’s disease (AD) is the most common form of dementia characterized by a prominent cognitive deterioration of sufficient magnitude to impair daily living. Increasing studies indicate that non-coding RNAs (ncRNAs) are involved in ferroptosis and AD progression. However, the role of ferroptosis-related ncRNAs in AD remains unexplored. Methods We obtained the intersection of differentially expressed genes in GSE5281 (brain tissue expression profile of patients with AD) from the GEO database and ferroptosis-related genes (FRGs) from the ferrDb database. Least absolute shrinkage and selection operator model along with weighted gene co-expression network analysis screened for FRGs highly associated with AD. Results A total of five FRGs were identified and further validated in GSE29378 (area under the curve = 0.877, 95% confidence interval = 0.794–0.960). A competing endogenous RNA (ceRNA) network of ferroptosis-related hub genes (EPT1, KLHL24, LRRFIP1, CXCL2 and CD44) was subsequently constructed to explore the regulatory mechanism between hub genes, lncRNAs and miRNAs. Finally, CIBERSORT algorithms were used to unravel the immune cell infiltration landscape in AD and normal samples. M1 macrophages and mast cells were more infiltrated whereas memory B cells were less infiltrated in AD samples than in normal samples. Spearman’s correlation analysis revealed that LRRFIP1 was positively correlated with M1 macrophages (r = -0.340, P < 0.001) whereas ferroptosis-related lncRNAs were negatively correlated with immune cells, wherein miR7-3HG correlated with M1 macrophages and NIFK-AS1, EMX2OS and VAC14-AS1 correlated with memory B cells (|r| > 0.3, P < 0.001). Conclusion We constructed a novel ferroptosis-related signature model including mRNAs, miRNAs and lncRNAs, and characterized its association with immune infiltration in AD. The model provides novel ideas for the pathologic mechanism elucidation and targeted therapy development of AD.